Properties of high-performance concrete with automobile grinding waste as replacement of fine aggregate. (2023) - Selvakumar, M.; Muthu Lakshmi, S.; Srinivasan, K.B.; Srinivasan, D.; Santhosh, T.
Abstract: The amount of waste generation in automobile industries during the manufacturing process is constantly increasing due to the increase in population. For each ton of steel usage, 0.1 tons of waste steel in the form of sludge is discarded as waste. That is collectively known as Automotive Steel Sludge (Auto-SS). The concrete which has increased strength, workability, high modulus of physical property, density (2400 kg/m 3 ), and durability is called High-Performance Concrete (HPC). The objective of this study is the utilization of waste steel sludge as a replacement for fine aggregate that can control environmental effects and scarcity of natural resource materials like sand. The physical properties of steel sludge showed more density when compared to the sand. It was a positive indication for producing High-Performance Concrete with Auto-SS. Replacement trials were carried out for M-sand with Auto-SS. Compressive strength was taken with a comparison of conventional concrete and M-sand replaced with Auto-SS concrete cubes. The compressive strength of normal concrete gives 61.80 MPa, but the replacement specimen gives 64.62 MPa which is higher than conventional. Thus the results of the tests in these studies show that usage of steel sludge for the replacement of fine aggregate in high-performance concrete can be used in real-life execution in the construction of heavily loaded structures like high-rise buildings, bridges, flyovers, offshore structures, and tunnels is a better way.